PENGARUH PENGGUNAAN METODE MAKE A MATCH TERHADAP MINAT BELAJAR SISWA MATA PELAJARAN AL-QUR’AN HADITS MATERI TAJWID KELAS V DI SD ISLAM KEBUNREJO GENTENG BANYUWANGI - Anis Fauzi; Ahmad Izza Muttaqin; Siti Aminah (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
This study aims to find out the influence of the use of make a match learning methods to students' learning interests in the subjects of the Quran Hadith tajwid material class V at SD Islam Kebunrejo Genteng Banyuwangi year 2019/2020, and to know the extent of the influence of learning methods on students' learning interests in the subjects of qur'an Hadith material Tajwid class V at SD Islam Kebunrejo Banyuwangi Year 2019/2020. This study uses a quantitative approach with this type of experimental research. The population in this study was all grade V students who numbered 23 students. Of these populations sampling using non probability sampling techniques, because the number of students is less than 30. In the process of collecting data using several methods, namely participatory observation methods, interview methods, inquiry methods, and documentation methods. The test of the inquiry's learning method makes fit and interest in students' learning using validity tests and reliability tests. The results of this study showed Chi Square count = 9,763 and chi square table = 3,841, then obtained r-count> r-table 9,763> 3,841. Thus Ho was rejected and Ha accepted, it can be concluded that there is an influence of the use of make a match learning methods to students' learning interests in the subjects of the Quran Hadith tajwid material class V at SD Islam Kebunrejo Genteng Banyuwangi year 2019/2020.